GAMBARAN RONTGEN TORAKS DIBANDINGKAN DENGAN TCM (TES CEPAT MOLEKULER) GENEXPERT PADA PASIEN TUBERKULOSIS PARU DI RSUD DR. M. HAULUSSY - Tandililing, Thristy; Jwantoro, Agus; Tentua, Vebiyanti; Sangadji, Astri; Nasrul, Hilda; Hataul, Is Asmaul (Fakultas Kedokteran Universitas Pattimura, 2024)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. This bacteria can attack all organs in the human body, especially the lungs. The source of transmission is a TB patient with a cough or sneeze. The main symptom of pulmonary tuberculosis is a cough that lasts for 2 weeks or more. This study aims to determine the picture of chest x-rays compared with the results of the Rapid Molecular Test examination in patients with pulmonary tuberculosis at RSUD Dr. M. Haulussy Ambon. This study is an analytic descriptive study with a cross-sectional approach. Sampling was conducted at the Medical Record Installation with a total sample of 63 patients. The results of the study were obtained based on the picture of the chest X-ray compared with the results of the GeneXpert TCM examination, the highest number was patients who had a thoracic X-ray picture of active old pulmonary TB with medium TCM GeneXpert results as many as 32 patients.